แนวคิดในการไตร่ตรองการสอนสำหรับนิสิตฝึกประสบการณ์วิชาชีพ - คล้ายมงคล ยุรวัฒน์ (Journal of Education Studies, Chulalongkorn University, 2019)
This article presents reflective teaching ideas for learning development and for student teachers in practicum. The reflective thought ideas were synthesized from the reflective ideas of John Dewey, the experiential learning of David Kolb, the reflective practice of Donald Schön, the ‘new’ conceptual framework for reflection in the pre-service teacher education of LaBoskey, the map of learning and the representation of learning in the reflection of Moon and others. The syntheses were then applied to develop four procedures of reflective teaching ideas for student teachers: revising, reflecting, reasoning, and improving. There is a table explaining the relationships between the reflection steps and other components.